3D axisymmetric MHD system with regularity in the swirl component of the vorticity. (15th June 2017) - Zhang, Zujin; Yao, Zheng-an
Abstract: This paper concerns with the regularity criteria for the 3 D axisymmetric MHD system. It is proved that the control of swirl component of vorticity can ensure the smoothness of the solution.